Bio-physical removal of heavy metal from aqueous solution. Issue 59 (19th December 2016) - Kutty, S.R.M.; Ezechi, E.H.; Khaw, S.G.; Lai, C.L.; Isa, M.H.
Abstract: The aim of this study was to compare the performance of a suspended growth bioreactor and a combined bio-physical bioreactor for Zn 2+ removal from aqueous solution. Two identical bioreactors (8.5 L each) were operated at a fixed HRT of 29.1 h. The suspended growth bioreactor was used as the control reactor and contained only sludge. The bio-physical bioreactor contains sludge and a low-cost adsorbent derived from groundwater treatment plant sludge. The influent Zn 2+ concentration was varied from 0.5 to 15 mg/L in 8 experimental phases. Influent and effluent Zn 2+ concentration was monitored daily. Phase 1 (day 1–15) and phase 2 (day 16–29) were used as acclimation period for both bioreactors, respectively. Results show that Zn 2+ removal increased with increasing influent Zn 2+ concentration from 0.5 to 1.0 mg/L (phases 3–4) but fluctuated thereafter for the suspended growth bioreactor. Zn 2+ removal in the bio-physical bioreactor increased with increasing influent Zn 2+ concentration from 0.5 to 10 mg/L (phases 3–7) and decreased with further increase in influent Zn 2+ concentration to 15 mg/L (phase 8). The effluent Zn 2+ concentration in phase 8 for the suspended growth and the bio-physical bioreactors were 58.7 and 90%, respectively. The higher removal of Zn 2+ in the bio-physical bioreactor was due to heavy metal tolerance and the resistance in heavy metal toxicity on the microbial community of the combined system.